THE ROLE OF TRIMETAZIDINE DRUG IN POST-MYOCARDIAL INFARCTION CONDITION - Shomirova Zulayxo Maxmud qizi (TADQIQOTLAR.UZ, 2024)
The efficacy of trimetazidine, an anti-ischaemic agent, has been largely assessed and presented in the international literature through its metabolic effects, selective and specific fatty acid oxidation inhibition and lack of haemodynamic effects in stable angina pectoris. As such, trimetazidine has opened up a new class of metabolic agents that reduce fatty acid oxidation: the 3-KAT (3-ketoacyl-CoAthiolase) inhibitors.The aim of this review article is to demonstrate the cardioprotective benefits of trimetazidine, and how this can be translated into positive effects in the treatment of cardiac disorders. Trimetazidine has been assessed in several double-blind randomised studies as a treatment of ischaemic heart disease or as an agent given prior to or during percutaneous transluminal coronary angioplasty, coronary artery bypass grafting and thrombolysis to prevent or limit ischaemia/reperfusion damage in the heart. All these studies demonstrate that trimetazidine protects the heart from the deleterious consequences of ischaemia by switching cardiac metabolism from fatty acid oxidation to glucose oxidation. Study results cast no doubts on the value of the cardioprotective effects of trimetazidine and support the fact that trimetazidine has a direct anti- ischaemic effect on human myocardial cells. Trimetazidine has proven antianginal efficacy, and can be also used in other cardiac diseases with ischaemic signs.